The upper Turonian (Cretaceous) Prionocyclus germari Zone of the Vocontian Basin, France, with description of Vocontiiceras vocontiense nov. gen. et sp. (Collignoniceratidae, Ammonoidea) - Diebold, Frédéric; Bengtson, Peter; Baudouin, Cyril; Tröger, Karl-Armin; Lees, Jacqueline A.; Bert, Didier (Cretaceous research, 2017)
The Prionocyclus germari Zone is recognized for the first time in the Vocontian Basin. The upper part of the “calcaires blancs à silex” of the western Dieulefit syncline is characterized by the zonal index and a diverse ammonite fauna, as well as inoceramids of the Mytiloides scupini Zone. The co-occurring heteromorph ammonites Hyphantoceras (Hyphantoceras) flexuosum (Schlüter, 1872) and H. (H.) ernsti Wiese, 2000 suggest a correlation with the Heteromorph Beds and the flexuosum Sequence of northern Germany. The co-occurrence of Prionocyclus germari (Reuss, 1845) and the bivalve Didymotis sp. in the overlying “grès jaunes” suggests a correlation with the Didymotis Sequence of northern Germany. The presence of the nannofossil Broinsonia parca expansa Wise & Watkins, 1983 and absence of younger marker species indicate the upper Turonian to lower Coniacian nannofossil zone UC9c. The boundary between the “calcaires blancs à silex” and the “grès jaunes” is interpreted as a sequence boundary linked to a eustatic rise of sea level. The event is correlated with the flexuosum-Didymotis sequence boundary of northern Germany and can be traced in northern Spain and the Czech Republic. Vocontiiceras vocontiense nov. gen. et sp. of the Family Collignoniceratidae shows a distinct ontogeny: an involute juvenile stage with Reesidites-like ornamentation and a single row of ventrolateral tubercles, and a smooth adult stage with a persistent keel and a short rostrum. The new species probably represents an evolutionary link between the subfamilies Collignoniceratinae and Barroisiceratinae.
Gesehen am 02.03.2018